Material properties of paras variety jamun fruit (Syzygium cumini L.) - Sardar, N R (Journal of Postharvest Technology, 2022)
Jamun (Syzygium cumini L.) is a popular indigenous fruit. Characterizing fruits is an important process that explains the individual characteristics of the different cultivars, as well as the features that influence the handling and development of the product. Improving the Jamun stock benchmark can increase their attention and prepare them to be more productive and profitable. The material properties values of jamun fruit of paras variety for weight, length, width and thickness obtained were found tobe 9.08 ±1.14 g, 29.58 ±1.23mm, 17.07 ±1.29 mm, 16.30 ±1.85, Value for bulk density and true density were found to be 1049±0.03 Kg/m3 and 1054±0.03 Kg/m3 respectively. The pulp yield and pulp to seed ratio were estimated as 72.17±1.46 and 2.82: 1, respectively. These properties were important to commercial aspects for storage, packaging, processing and transportations.